Respuesta :

i hope it is helpful

thank you
Ver imagen Emperial143

Answer:

see explanation

Step-by-step explanation:

Cross- multiply

Noting that x ≠ [tex]\frac{5}{2}[/tex] as this would make the denominators on both sides zero, that is undefined

(x² - 2)(6x - 15) = (x + 3)(10 - 4x) ← expand parenthesis on both sides

6x³ - 15x² - 12x + 30 = 10x - 4x² + 30 - 12x = - 4x² - 2x + 30

Subtract - 4x² - 2x + 30 from both sides

6x³ - 11x² - 10x = 0 ← in standard form

Factor out x from each term

x(6x² - 11x - 10) = 0

x(3x + 2)(2x - 5) = 0 ← in factored form

Equate each factor to zero and solve for x

x = 0

3x + 2 = 0 ⇒ 3x = - 2 ⇒ x = - [tex]\frac{2}{3}[/tex]

2x - 5 = 0 ⇒ 2x = 5 ⇒ x = [tex]\frac{5}{2}[/tex]

Solutions are x = 0, x = - [tex]\frac{2}{3}[/tex]

ACCESS MORE